Influence of Leadership Style and Work Culture on Organizational Performance Through Work Motivation at BNN RI - Yuli Tri Hastuti; Partogi Samosir (Indonesian Journal Economic Review (IJER), 2026)
This study examines the influence of leadership style and work culture on organizational performance at the Badan Narkotika Nasional Republik Indonesia (BNN RI), with work motivation as a mediating variable. Although BNN RI has demonstrated significant operational achievements in narcotics enforcement, internal organizational dynamics such as leadership rotation, cultural alignment, and fluctuating employee motivation may affect long-term institutional performance. This research adopts a quantitative explanatory design using survey data collected from 93 civil servants at the BNN RI headquarters, selected through simple random sampling. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to evaluate both measurement and structural models. The results indicate that leadership style has a positive and significant direct effect on organizational performance and work motivation. Work culture significantly influences work motivation but does not directly affect organizational performance. Work motivation has a positive and significant impact on organizational performance; however, it does not mediate the relationship between leadership style or work culture and organizational performance. The model demonstrates moderate explanatory power, indicating that other variables beyond the proposed model also contribute to performance outcomes. These findings suggest that strengthening leadership quality and fostering a constructive work culture are critical for enhancing organizational performance in public sector institutions, particularly within law enforcement agencies operating in complex and high-risk environments.